Isolation of extended-spectrum beta-lactamases producing strains on effluent of state hospital from Boa Vista-RR - Brandão, Marcia Brazão e Silva; Capucho, Derlano Bentes; Aguiar, Edimilla Carneiro da Cunha; Assis, Rafael Nascimento de; Granja, Fabiana (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
The extended spectrum beta-lactamase (ESBL) producing bacteria are widespread in hospital environments. The incorrect disposal of clinical waste in hospital effluents, allows them to present high concentrations of bacteria with antimicrobial resistance profiles that present an environmental risk to the extent that they allow the dissemination. This research covers the characterization of the presence of multi-resistant antimicrobial bacteria in strains isolated from hospital effluents, whose associated risks include the spread of pathogenic microorganisms in the environment. To complete this research, the proposed objectives were: characterization of the hospital effluent strains generated by the General Hospital of Roraima (GHR) and research of the resistance genes responsible for ESBL coding and hydrolysis to the antimicrobials of the class of cephalosporins, penicillins and monobactams. Samples were collected from the hospital septic tank from June 2014 to June 2016, submitted to molecular identification for the detection of genes through the polymerase chain reaction (PCR). The results showed the presence of ESBL in all of the collected tanks and a multi-resistance profile. ESBL genes were identified on isolated frequencies and they were combined. The results indicated the widespread dissemination of the ESBL genes in the GHR effluent.